2020
DOI: 10.1111/jcmm.15205
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the relationship between FLI1 and immune infiltrate level in tumour immune microenvironment for breast cancer

Abstract: Breast cancer is the most common cancer and the leading cause of cancer death among women in the world. Tumour-infiltrating lymphocytes were defined as the white blood cells left in the vasculature and localized in tumours. Recently, tumourinfiltrating lymphocytes were found to be associated with good prognosis and response to immunotherapy in tumours. In this study, to examine the influence of FLI1 in immune system in breast cancer, we interrogated the relationship between the FLI1 expression levels with infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 113 publications
1
11
0
Order By: Relevance
“…Breast cancer (BC) has remained the most frequently diagnosed malignancy and one of the leading causes of cancer-related deaths among females worldwide. 1 The most widely used clinical classification of BC is based on the expression of progesterone receptor (PR), estrogen receptor (ER), and human epidermal growth factor receptor 2 (Her-2), which are considered as classical prognostic indicators and therapeutic targets. 2 , 3 Despite limited progress in BC treatment with drugs against these targets, such as anti-Her-2 targeted therapy (trastuzumab), some patients are still predisposed to advanced stages attributing to the strong heterogeneity of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) has remained the most frequently diagnosed malignancy and one of the leading causes of cancer-related deaths among females worldwide. 1 The most widely used clinical classification of BC is based on the expression of progesterone receptor (PR), estrogen receptor (ER), and human epidermal growth factor receptor 2 (Her-2), which are considered as classical prognostic indicators and therapeutic targets. 2 , 3 Despite limited progress in BC treatment with drugs against these targets, such as anti-Her-2 targeted therapy (trastuzumab), some patients are still predisposed to advanced stages attributing to the strong heterogeneity of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the FLI1 was enriched in immune biological processes with 28 immune cell in ltrations. Furthermore, the FLI1 was correlated with the immune-related genes in BRCA [31]. In the human T-cell line Jurkat, both isoforms of FLI1 (p51, p48) were phosphorylated on serine residues, which was increased by a Ca 2+ -mediated process, and inhibited by protein phosphatase 2A [32].…”
Section: Discussionmentioning
confidence: 99%
“…In PE, when CS are elevated, Na/K-ATPase is depressed and Fli1 is low this results in the occurrence of a phenotype associated with a significantly lower incidence of breast cancer [ 59 , 60 ] ( Figure 2 ). At the same time in breast cancer patients ( Figure 2 ) CS and Na/K-ATPase are regular [ 61 , 62 , 63 , 64 , 65 ] and Fli1 is high [ 66 , 67 , 68 ]; i.e., as if patients with PE administered an anti-CS antibody. Could it be true for the other types of cancer?…”
Section: Immunoneutralization Of Cardiotonic Steroidsmentioning
confidence: 99%